Optimasi Operasi Irigasi pada Kondisi Darurat Pasca Bencana Gempa di Daerah Irigasi Gumbasa, Sigi, Sulawesi Tengah - Haryo Istianto; Hanhan Ahmad Sofiyuddin (Balai Teknik Irigasi, 2019)
Earthquake incident in Sigi District, Central Sulawesi has damaging the Gumbasa Irrigation Scheme. Rehabilitation of irrigation network will be carried out gradually starting at firtst stage from the intake until the canal section of BGKn 8 (Sibalaya) which affected by the liquefaction. Irrigation operations need to be carried out gradually for the section which has been rehabilitated and ready to be operated so that the local community can immediately grow crops and not lose their livelihood. Nevertheless, the service area and required canal discharge will be much lower than the design so it will cause some water distribution problems. This research was conducted to formulate a pattern of irrigation operations in Gumbasa Irrigation Scheme in emergency situations where the canal discharge is much lower than the designed. Research was conducted by means of data collection and formulation of irrigation operation scenarios through hydraulic analysis. Simulated scenario was an operation without optimization, optimization by using existing sluice gate, and optimization using the skot beam. The results showed that irrigation operation without optimization can not be done because the elevation of water can not rise and flows to the secondary canal due to the large primary canal dimension. The use of a sluice gate optimization can only elevate water elevation by ±1 m from the base of the canal. In addition, closing the sluice gate can result in overflow in some canal segment. In the last scenario, utilization of the skot beam for optimization is the best solution. Skot beams can elevate water at the required height. Skot Beam is a infrastructure which quite good for a temporary irrigation operation where the water level can be adjusted even though the discharge is relatively small.